Cost of corporate financial crime / Wan Nailah Abdullah and Roshima Said - Abdullah, Wan Nailah; Said, Roshima (Faculty of Accountancy, UiTM Kedah, 2019)
Corporate financial crimes, for instance, economic exploitation, fraud, and tax evasion, to name a few, bring serious consequences for the society and citizenry because, through these crimes, companies violate the revenue code of the law, and hence, are allowed to raise their profits, reduce their tax payments, and even underpay their employees. Three main costs that can be associated with corporate financial crime, are the direct financial costs, physical costs, and damage to society’s moral values (McKendall, 1990). Direct financial costs are the most obvious costs of corporate financial crime. In the United States alone, for instance, corporate financial crime costs the country not less than USD200 to USD600 billion annually, more than any other crimes put together (Hartley, 2008). That is only moneywise, and it is already known that there are other consequences such crimes bring beyond the monetary numbers. The average fraud loss suffered by a company in Malaysia was estimated to be RM7.7 million per year by PricewaterhouseCoopers (2009) with 6000 cases reported yearly (Clarence, 2005).